The Vital Role of Cytotoxic T Cells in Iraqi COVID-19 Patients and Vaccinated Individuals - Mutlaq, Sally Taleb; Al-azzawi, Raghad Harbi (Iraqi Journal of Science, 2026)
Coronaviruses, including the novel SARS-CoV-2, have led to a global pandemic, emphasizing the crucial role of T cells in mounting effective immune responses. This study investigates the correlation between cytotoxic T cells (CD8), vitamin D3 (VD3), and C-reactive protein (CRP) levels in a sample of Iraqi COVID-19 patients and vaccinated individuals. A total of 120 participants were included, comprising COVID-19 patients and vaccinated individuals. Samples were collected between October 2021 and February 2022. Reverse transcriptase polymerase chain reaction (RT-PCR) was used for COVID-19 diagnosis. VD3 and CD8 levels were determined using enzyme-linked immunosorbent assay (ELISA) kits, while CRP levels were measured via the ICHROMA system. Elevated VD3 levels were observed in COVID-19 patients (G1) and vaccinated individuals (G2), while CRP levels were notably higher in G1. CD8 levels were elevated in G1, G2, and individuals previously infected for 3-6 months (G3). While a significant correlation between CD8 and VD3 was noted, the association with CRP was not as pronounced. The findings underscore the importance of cytotoxic T cells in both natural and vaccinated immunity against COVID-19, highlighting potential avenues for further research and therapeutic interventions.